The effect of make a match method on students’ cognitive learning outcome at madrasah ibtidaiyah - Masnun Baiti; Mira Wulan Dari; Maryamah Maryamah; Dian Andesta Bujuri; Agra Dwi Saputra; Nurlaila Nurlaila; Baharudin Baharudin (Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of implementing the Make a Match instructional method on student learning outcomes in the subject of Aqidah Akhlak. Employing a quantitative approach with a quasi-experimental design, the research was conducted with a sample of 47 fifth-grade students at Madrasah ibtidaiyah Ahliyah II Palembang. The experimental group consisted of 23 students from class VD, while the control group included 24 students from class VE. Data collection methods included tests, classroom observations, and documentation. The test instruments were subjected to validity and reliability testing, as well as item difficulty and discrimination index analysis. Data were analyzed using an Independent Samples t-test. The findings indicate the following: (1) Prior to the implementation of the Make a Match method, only 3 students (13%) in the experimental group achieved mastery, while 20 students (86.9%) did not. (2) After the intervention, 16 students (69.6%) in the experimental group reached the mastery level, with 7 students (30.3%) remaining below the threshold. (3) In the control group, which did not receive the intervention, only 7 students (29.2%) achieved mastery, while 17 students (70.7%) did not. (4) Hypothesis testing using the Independent Samples t-test yielded a significance value of 0.000 (< 0.05), indicating a statistically significant difference between the two groups. These results support the conclusion that the Make a Match learning method has a positive and significant impact on student achievement in Aqidah Akhlak, particularly in enhancing mastery of moral and religious concepts.